2019
DOI: 10.1097/wco.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

Visual function in children with primary brain tumors

Abstract: Purpose of review: To review the recent advances in understanding how primary brain tumors affect vision in children. Recent findings: Children with primary brain tumors may have vision loss due to involvement of their afferent visual pathways or from papilledema. These vision deficits may go unrecognized until later in life, years after treatment of the primary lesion. Strabismus and cranial nerve palsies may occur as a result of brain tumors. Ophthalmologists can monitor and treat young children at risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Visual problems may be reversible in early stages of visual impairment. Therefore, timely monitoring of visual function and early detection of visual impairment in children with CP is of major importance to preserve visual function and provide adequate treatment [12,13,17,18,20]. In children with irreversible visual impairment, timely referral for visual rehabilitation may reduce the adverse effects of visual impairment on health and/or vision related quality of life [115,116].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Visual problems may be reversible in early stages of visual impairment. Therefore, timely monitoring of visual function and early detection of visual impairment in children with CP is of major importance to preserve visual function and provide adequate treatment [12,13,17,18,20]. In children with irreversible visual impairment, timely referral for visual rehabilitation may reduce the adverse effects of visual impairment on health and/or vision related quality of life [115,116].…”
Section: Discussionmentioning
confidence: 99%
“…Damage of the visual pathway commonly manifests as decreased visual acuity (VA), visual field (VF) defects, typically bitemporal hemianopia, and/ or abnormal pupillary reponses [5][6][7][8][9][10][11]. Increased intracranial pressure as a result of obstructive mass effect of the tumour can lead to papilledema with subsequent optic atrophy and permanent vision loss as potential complications [8,12,13]. In addition, therapeutic interventions for CP such as tumour resection or post-surgical radiation therapy can lead to further visual loss.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, survivors of a brain tumor are at risk for severe late effects of the disease and its treatment [5]. Visual impairment is one of these severe late sequelae of a pediatric brain tumor [6, 7]. It is reported that the harmful influence of the disease and / or its treatment on visual functioning has great impact on the general psychomotor development, school participation and societal participation later in life [7, 8].…”
Section: Introductionmentioning
confidence: 99%